AN EVALUATION OF ONLINE ARCHITECTURE DESIGN STUDIOS DURING THE COVID-19 PANDEMIC - Widiyani Widiyani; Yorangga Citra Arundati; Margaret Yudhia Aditama; Witriani Witriani (Department of Architecture, Universitas Tanjungpura, 2023)
During the